The little mermaid (China : Igloo books, 2017)
The Little Mermaid by Hans Christian Andersen is a fairytale about a mermaid who falls in love with a human. The plot of Andersen's fairytale is set in motion when the Little Mermaid visits the surface of the sea to observe life on land; this is a privilege afforded to mermaids once a year after the age of 15. When the Little Mermaid surfaces from the ocean, she sees a prince whom she falls in love with and later rescues from a shipwreck. As the plot develops, the Little Mermaid sacrifices her comfortable life as a mermaid to transform into a human in an attempt to win the affection of the prince. Ultimately the Little Mermaid is faced with a decision to either murder her beloved or die. Thematically, Andersen's story is one of love and self-sacrifice. Disney's adaptation of Andersen's The Little Mermaid revitalized the popular fairytale for a modern audience. Disney cut many of the violent details and subversive themes of Andersen's original work to increase the story's marketability. Notable differences between Disney's The Little Mermaid and Andersen's original story include character names, the nature of life on land, the nature of the Little Mermaid's transformation (both to a human and back to a mermaid), and the marriage between the prince and his bride.
Keywords: English - fiction; Fiction- book; Board - book